Lactato sanguíneo em cães com insuficiência cardíaca congestiva decorrente de degeneração valvular mitral - Silva Filho, Jorge Cardoso da [UNESP] (2014)
This study was aimed at characterizing the concentration of serum lactate in dogs with varying stages mitral valve degeneration, searching for a correlation between such parameter and the electrocardiographic, radiographic, echocardiographic and blood pressure data, as to investigate its value as a diagnostic indicator of tissue hypoperfusion in dogs with heart failure. The analyses of the serum concentration of lactate disclosed results estatistically higher in dogs belonging to CHF class II as compared to control animals, as well as between class IIIa dogs as compared to controls, class Ia, and class Ib dogs. However, the results of class II dogs were similar to those of classes Ia and Ib animals. Also, no difference was documented between the results of classes II and IIIa dogs. A positive correlation was identified between serum lactate concentration and the left ventricular internal diameter, fractional shortening, and left atrium-to-aorta ratio. A positive correlation was also observed between serum lactate and mean heart rate, VHS, and P wave amplitude. A negative correlation was documented between serum lactate and systolic blood pressure. A larger area under the ROC curve was disclosed for the jugular lactate, which showed the concentration of 3,25 mmol/L to provide the highest sensibility and specificity in differentiating healthy dogs from those presenting CHF. The results support that blood lactate increases as heart failure worsens